가압가열 및 Microwave 처리가 쿠키의 품질에 미치는 영향 - 강보경(Bo-Kyeong Kang); 김꽃봉우리(Koth-Bong-Woo-Ri Kim); 정슬아(Seul-A Jung); 김현지(Hyun-Ji Kim); 정다현(Da-Hyun Jeong); 박시우(Si-Woo Bark); 최정수(Jung-Su Choi); 최호덕(Ho-Duk Choi); 안동현(Dong-Hyun Ahn) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2013)
This study was conducted in order to determine the effect of autoclave and microwave treatments on cookies. Wheat dough was treated in an autoclave (30 min), a microwave (1 min), and both autoclave and microwave (30 min/1 min). The treated dough was baked or non-baked and cookies quality was assessed. The pH, moisture content, color, and texture were measured, and sensory evaluation was performed. The pH showed a slight increase when dough was treated in a microwave (before baking) and decreased in both the autoclave and autoclave/microwave (after baking) treatments. The moisture content showed a significant increase, compared to the control, in autoclave treatments. Regarding surface color of cookies, lightness was decreased in all treatments and redness was higher compared with the control, except for microwave (before baking), and yellowness was lower compared to the control, except for microwave treatment (after baking). Hardness, gumminess, chewiness, and shear force showed a significant increase when dough was treated in an autoclave/microwave (after baking) compared to the control. In the sensory evaluation, color, taste, texture, shape, and overall preference of cookies treated with an autoclave/microwave (after baking) showed a low score. These results suggest that autoclaving and microwaving may reduce the quality of bread and that preparation of countermeasures is necessary. 박력분을 이용해 제조한 쿠키 반죽에 microwave, 가압가열, microwave 및 가압가열 병행 처리 후 오븐에 굽기 전후의 쿠키의 일반 특성과 품질에 미치는 영향을 알아보았다. 쿠키의 pH는 microwave 1분 처리한 경우 무처리구에 비해 약간 증가하였고, microwave 1분 처리 후 구운 경우와 가압가열 및 microwave 병행처리 후 구운 경우 감소함을 보였다. 수분 함량은 반죽에 가압가열 처리했을 경우 상당히 증가하였다. 쿠키의 색도 측정 결과 외부색에서 명도는 무처리구에 비해 모든 처리구에서 감소하였고, 적색도는 microwave 1분 처리한 경우를 제외하고 모든 처리구에서 무처리구에 비해 높은 값을 보였으며 황색도는 microwave 1분 후 구운 경우를 제외하고 무처리구에 비해 낮은 값을 보였다. 물성 측정 결과, 경도, 검성, 씹힘성, 전단력에서 가압가열 및 microwave 병행처리 후 구운 처리구가 가장 많은 증가를 보였다. 관능평가에서는 무처리구가 전체 항목에서 가장 높은 점수를 받았고, microwave 1분 처리 후 구운 경우가 무처리구와 유사한 기호도를 보임을 확인하였으며, 선행 연구에서 밀 gliadin의 항원성을 감소시키는데 효과가 좋았던 가압가열 및 microwave 병행처리구의 경우 색, 형태, 질감, 전체적 기호도에서 낮은 점수를 받았다. 따라서 가압가열 및 microwave 병행처리구에 대해 색, 형태, 질감, 전체적 기호도를 개선시킬 수 있는 대책을 마련한다면, 알레르기성이 저감화된 제품 개발에 적합할 것으로 사료된다.